Penerapan Model Pembelajaran Kooperatif Tipe Group Resume Untuk Meningkatkan Minat Dan Hasil Belajar Siswa Pada Mata Pelajaran Geografi Siswa Kelas X IPS 1 SMA Negeri 10 Kota Jambi - Sinur Manulang (Jurnal Ilmiah Dikdaya, 2021)
This research aims to increase interest and learning outcomes in geography subjects in class X IPS 2 SMAN 10 Jambi in the 2018/2019 academic year through the application of the Group Resume type cooperative learning model. This research is a Classroom Action Research which was conducted in two cycles. Each cycle consists of planning, implementing, acting, observing and reflecting. The population in this study were students of class X IPS 2 SMAN 10 Jambi with a total of 30 students. The main data collection techniques in this study were observation, tests, and questionnaires, while the supporting data collection techniques used interviews and documentation. Data analysis using qualitative and quantitative descriptive analysis techniques. The results of this reaserch that the application of the cooperative learning model type Group Resume can increase the interesting and learning outcomes of students in geography in class X IPS 2 SMAN10 Jambi. In the first cycle, the students' interest in learning with good criteria was 66.60%, increasing to 86.67% in the second cycle. In the pre-action learning outcomes of students showed an average of 70.13, increased to 76.4 in cycle I, and increased to 87.06 in second cycle. The conclusion of this study is the application of the cooperative learning model type Group Resume can increase interesting and student learning outcomes in geography in class X IPS 2 SMAN 10 Jambi.